Word events perspectives on verbal notation - Lely, John 1976-; Saunders, James 1972- (Continuum, 2012)
"Verbal notation has emerged since the 1950s as a prominent medium in the field of experimental music, as well as in related areas of arts practice involving performance and object making ... This book examines the use of English grammar in verbal notation, with numerous examples of usage from specific verbal scores. Commentaries explore the compositional strategies and performance practice of particular works in key essays ... from composers, artists and performers"--P. 4 of cover